2010
DOI: 10.1111/j.1365-2133.2010.09821.x
|View full text |Cite
|
Sign up to set email alerts
|

Reticular grey-blue areas of regression as a dermoscopic marker of melanoma in situ

Abstract: Frequency, morphology, extent and distribution of regression vary according to melanoma thickness and diameter. Lesions with reticular blue regression and light brown areas should undergo surgical excision for the suspicion of MIS. Moreover, the identification of the reticular pattern of blue regression can be considered a significant discriminator and a reliable predictor of MIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 38 publications
4
47
1
Order By: Relevance
“…We identified the reticular pattern of grey-blue regression as a significant discriminator and a reliable predictor of MIS [11]. Moreover, we showed that the dermoscopic island, a well-circumscribed lesion area showing a uniform dermoscopic pattern which differs from the one present in the rest of the lesion, is characteristic of thin MMs, especially in situ ones, arising on a naevus [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified the reticular pattern of grey-blue regression as a significant discriminator and a reliable predictor of MIS [11]. Moreover, we showed that the dermoscopic island, a well-circumscribed lesion area showing a uniform dermoscopic pattern which differs from the one present in the rest of the lesion, is characteristic of thin MMs, especially in situ ones, arising on a naevus [12].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently described some dermoscopic aspects peculiar for MIS and initial MMs, such as reticular grey-blue areas, the dermoscopic island and atypical aspects of the network [11,12]. We identified the reticular pattern of grey-blue regression as a significant discriminator and a reliable predictor of MIS [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). 28 The fading of the pigment network or of other dermoscopic structures results in areas of structureless light brown pigmentation. 29 This reticular-type of regression can be found in so-called slow-growing melanomas that are characterized dermoscopically by the simultaneous presence of network and regression.…”
Section: Regression (Flat Blue-white Structures)mentioning
confidence: 99%
“…This reticular pattern can serve as a distinguishing characteristic of MIS. 75 The distribution of blue areas (center vs. periphery) is similar in MIS and MM. Peppering, or scattered blue-gray granules within an area of hypopigmentation, can be seen in similar proportions in both types of lesions.…”
Section: Clinical Features Key Pointsmentioning
confidence: 89%